Analisis Forensics Untuk Mendeteksi Pemalsuan Video - Umar, Rusydi; Fadlil, Abdu; Putra, Alfiansyah Imanda (STIKOM Tunas Bangsa Pematangsiantar, 2019)
The current technology is proving that the ease with which crimes occur using computer science in the field of video editing, in addition from time to time more and more video editing software and increasingly eassy to use, but the development of this technology is widely misused by video creators to manipulate video hoaxes that cause disputes, so many video cases are spread which cannot be trusted by the public. Counterfeiting is an act of modifying documents, products, images or videos, among other media. Forensic video is one of the scientific methods in research that aims to obtain evidence and facts in determining the authenticity of a video. This makes the basis of research to detect video falsification. This study uses analysis with 2 forensic tools, forevid and VideoCleaner. The result of this study is the detection of differences in metadata, hash and contrast of original videos and manipulated videos.